THE MEDIA ENVIRONMENT AND ANTI-VACCINATION MOVEMENTS - Kasarda, Martin (European Scientific Journal, ESJ, 2013)
The newest media (e.g. the internet) allow the spread of conspiracy theories, entirely or partially fictional information at an unprecedented rate. Anti-vaccination movements across the globe currently use the most modern available communications technology to promote their ideology, to attack the public and to attack systematic solutions that individual governments use as parts of their national vaccination programs. This paper wishes to focus on the issue of freedom of information, yet at the same time point out a rift that exists between factual data and factually incorrect reports that are being spread via the internet, a rift that may be the cause of serious public health issues.